Improving cadre competence through anthropometry training in Mawang Village, Gowa Regency, Indonesia - Raodhah, Sitti; Satrianegara, Muhammad Fais; Rusmin, Muhammad; Adnan, Yudi; Surahmawati, Surahmawati; Arranury, Zilfadhilah; Rahma, Nur (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
A common issue in public health services is the limited knowledge and skills of posyandu cadres in conducting accurate anthropometric measurements, which affects the assessment of children's nutritional status. This community service program through training aims to improve the competencies of posyandu cadres in anthropometric measurements in Mawang Village, Somba Opu District, Gowa Regency. Anthropometric measurements are essential for assessing children's nutritional status and overall community health. The participatory training method involved cadres actively in every stage, from planning to evaluation. The training was conducted on September 14, 21, and 28, 2024, at Nurul Huda Mosque, with the participation of 35 posyandu cadres. The training materials included anthropometric measurement theory, correct techniques, and practical demonstrations. The evaluation results showed a significant increase in cadres' knowledge, with an average pre-test score of 13.37 and an average post-test score of 14.60 (p-value 0.000). This increase demonstrates the effectiveness of the training in enhancing cadres' understanding of anthropometric measurements, which is expected to contribute to improving the quality of health services at posyandu. This study emphasizes the importance of continuous training for posyandu cadres to support public health improvement efforts.